Toxicidade do mercúrio em ratas virgens, gestantes e lactantes: efeito protetor do zinco e da N-acetilcisteína - Oliveira, Vitor Antunes de (2016)
Mercury (Hg) is a divalent metal found liquid at room temperature without biological functions and anthropogenically released in industrial, agricultural activities and burning of fossil fuels. Toxic effects caused by exposure to this metal are related to the interaction of different biochemical processes due to its affinity for sulfhydryl groups (SH). This damage depends on the time of exposure and the development period in which the individuals are exposed. Thus, the aim of this study was to evaluate the effects of a single subcutaneous dose of inorganic Hg in virgin, pregnant and lactating rats, as well as the protective effect of zinc (Zn) and N-acetylcysteine (NAC). For this, three experimental protocols were used: I) Virgin female rats were treated with ZnCl2 (27 mg/kg) and/or NAC (5 mg/kg) or saline (0.9%) and 24 hours after with HgCl2 (5 mg/kg) or saline (Article 1). II) Pregnant or lactating rats were treated with ZnCl2 (27 mg/kg) and/or NAC (5 mg/kg) or saline (0.9%) and 24 hours after with HgCl2 (10 mg/kg) or saline (manuscript I). III) Renal and hepatic analysis of virgin, pregnant and lactating rats exposed to a dose of HgCl2 (5 mg/kg) or saline (manuscript II). In all protocols euthanasia was performed 24 hours after the last treatment and the tissues removed and prepared for analysis. Protocols I and II focused primarily on biochemical parameters in different tissues and protocol III in morphological evaluations and protein expression in the kidneys and liver. Virgin rats exposed to Hg showed inhibition of the δ-aminolevulinic acid dehydratase (δ-ALA-D) activity in all tissues analyzed, changes in serum markers of hepatic (alanine aminotransferase [ALT] and aspartate aminotransferase [AST]) and renal (creatinine and urea) damage, morphological damage, and changes in proteins related to oxidative stress expression, for instance, mitofusin 2 (MFN2), inducible nitric oxide synthase (iNOS), heat shock protein 27 (HSP27) and glucose regulated protein 75 (GRP75). Pregnant and lactating rats exposed to mercury showed milder changes than virgin rats, including no inhibition of hepatic δ-ALA-D or alterations of proteins related to oxidative stress and few morphological damage. Pregnant and lactating rats still showed physiologically higher levels of metallothionein (MT) in the liver and larger glomerulus diameter than virgin rats. The results suggest greater resistance of pregnant and lactating rats to Hg compared with virgin rats. This difference may be related to increase of hepatic MT levels induced by pregnancy and lactation. This protein is synthesized in the liver and plays an important chelator role,. making substances, such as Hg, less harmful. The treatment with Zn and NAC showed promising results against damage caused by Hg, probably by induction of MT synthesis caused by Zn and by chelating action of NAC. In both situations occur the capture of Hg. The metal bound to MT or NAC is neutralized and consequently has lower toxicity effects.